2012
DOI: 10.1007/978-3-642-35506-6_23
|View full text |Cite
|
Sign up to set email alerts
|

Memory Issues of Intelligent Agents

Abstract: Abstract. Theoretical models of artificial general intelligence, such as AIXI [3], typically consider an intelligent agent to have unlimited computational resources, allowing it to keep a perfect memory of its entire interaction history with its environment. In the real world, an agent's memory is part of the environment, which means that the latter can modify the former. This paper develops a theoretical framework for examining the implications of such real-world memory on universal intelligent agents. Within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…One of the conclusions reached by the authors was the value of a "chief memory officer" or an organizational historian to act as a human agent and champion of organizational memory. It has since been identified that artificial IAs may aid human agents in the preservation of organizational memory (Orseau and Ring, 2012;Ring and Orseau, 2011).…”
Section: Related Literaturementioning
confidence: 99%
“…One of the conclusions reached by the authors was the value of a "chief memory officer" or an organizational historian to act as a human agent and champion of organizational memory. It has since been identified that artificial IAs may aid human agents in the preservation of organizational memory (Orseau and Ring, 2012;Ring and Orseau, 2011).…”
Section: Related Literaturementioning
confidence: 99%
“…The notation is similar to that of Orseau & Ring [5,8,6]. At some time t the agent outputs actions a t ∈ A to the environment, which returns observations o t ∈ O to the agent.…”
Section: Notationmentioning
confidence: 99%
“…Thinking of ρ as a non-universal but accurate model of the real world is also acceptable (although arguably non-realistic). 6 This is an uncomputable definition, but the solution of this equation is a computable optimal resource-bounded agent.…”
Section: Self-modifying Resource-bounded Universal Intelligencementioning
confidence: 99%
See 2 more Smart Citations